EVALUATION OF ANTIBACTERIAL AND HAEMOLYTIC ACTIVITY OF PHYTOCHEMICALS FROM FRESHWATER MICROALGA, EUGLENA VIRIDIS (EHREN) - Pradhan, Jyotirmayee; Das, Basanta Kumar; Sahu, Swagatika (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: The main aim of this research work was to evaluate the antibacterial and haemolytic activities of different extracts of Euglena viridis (E. viridis), a freshwater microalga. Methods: The solvent extraction has been followed by a preliminary screening of phytochemicals. The ethanolic extract, Eu(EtOH) was chromatographed on a silica gel column. The column was eluted with hexane and then with ethyl acetate/hexane mixtures of increasing polarity, 16 fractions (Ef1-Ef16) were collected and grouped according to their TLC (Thin layer chromatography). Antibacterial activities of different fractions of E. viridis against Pseudomonas putida (P. putida) ATCC49828, P. aeruginosa MTCC 35672, Aeromonas hydrophila (A. hydrophila) MTCC 646, ATCC 49140, eleven strains of Staphylococcus aureus (S. aureus) and thirteen strains of Flavobacterium columnare (F. columnare) was done using disc diffusion methods. Haemolytic activity was carried out by using blood agar plate method. The MIC (Minimum inhibitory concentration) values of active fractions were determined by the broth dilution method. Results: The results showed that the Eu(EtOH) poses significantly (p≤0.5) higher zone of inhibition (14.0±0.28, 13.5±0.28 mm) against FLV8 and FLV9 respectively. Three strains of Flavobacterium (FLV5, FLV6 and FLV10) were highly sensitive (zone size, 17 mm, 17.5 mm) towards 30% EA: Hex chromatographic eluents (Ef11) with lowest MIC values, e. i 60 µg and 30 µg respectively. Two chromatographic fractions, Ef11 and Ef13 were highly effective (zone size, 14.5 mm and 13.5 mm) against S. aureus (SA5) with lowest MIC value (60µg). Haemolytic activities of all the algal extracts were noticed that both Eu(EtOH) and methanolic extract, Eu(MeOH) of Euglena gives negative results. Conclusion: These findings suggest that the extract obtained from E. viridis have active substances contributing to the increasing antibacterial potential.